Sebuah Sifat Ganda Napoleon: Analisis Jungian tentang Animal Farm - Lyandi Putra, Yakub; Shenny Ayunuri Beata (e-LinguaTera, 2024)
This research explores the psychological underpinnings of Napoleon, one of the characters in George Orwell’s Animal Farm. Using a Jungian psychoanalytic approach, the study investigates the interplay between Napoleon's personality of shadow and persona. The research aims to understand how these psychological constructs are portrayed in the novel and the impact of the narrative’s plot development. Through a descriptive qualitative analysis, the novel acts as a source of primary data in the form of dialogues, statements, and descriptions. Meanwhile, secondary data was sourced from books, e-books, articles, and websites. Data was analyzed with the thematic data analysis method presented in the form of narrative text, opinions, and ideas in order to understand the concept of shadow and persona. The research found that Napoleon’s shadow personality emerged as a manifestation of his underlying motives, characterized by hypocrisy, cunning, ruthlessness, insecurities, and manipulation. Conversely, his persona is presented as visionary, responsible, infallible, benevolent, and full of potential. The study reveals the significant impact of Napoleon’s shadow and persona on the other animals on the farm. The two aspects of his personality lead to the division of idealism, loss of freedom, and manipulation of Farm’s history. These findings contribute to a deeper understanding of the novel’s theme and the psychological dynamics at play in totalitarian regimes.